MLCC offers Mandarin language to staff - UMP, PNC
Universiti Malaysia Pahang (UMP)'s Mandarin Language and Culture Centre (MLCC) had taken the initiative to introduce the language among staff in its efforts to improve credibility and ability of mastering Mandarin as a third language. Centre for Modern Languages and Human Sciences (PBMSK) Dean, Professor Dr. Abdul Jalil Borham said the objective was to improve the staff’s communication skills in many languages.